2017
DOI: 10.1158/1078-0432.ccr-17-1260
|View full text |Cite
|
Sign up to set email alerts
|

A Phase II Trial of Neoadjuvant MK-2206, an AKT Inhibitor, with Anastrozole in Clinical Stage II or IIIPIK3CA-Mutant ER-Positive and HER2-Negative Breast Cancer

Abstract: Hyperactivation of AKT is common and associated with endocrine resistance in estrogen receptor-positive (ER) breast cancer. The allosteric pan-AKT inhibitor MK-2206 induced apoptosis in -mutant ER breast cancer under estrogen-deprived condition in preclinical studies. This neoadjuvant phase II trial was therefore conducted to test the hypothesis that adding MK-2206 to anastrozole induces pathologic complete response (pCR) in mutant ER breast cancer. Potential eligible patients with clinical stage II/III ER/HER… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(56 citation statements)
references
References 45 publications
4
51
0
1
Order By: Relevance
“…62 There were no pathological complete responses (pCR) in the ERpositive population, and there was no additional suppression of tumor cell proliferation with the addition of MK-2206. A single-arm, phase 2 neoadjuvant clinical trial was conducted using the AKT inhibitor MK-2206 in combination with anastrozole in advanced breast cancer patients with a PIK3CA mutation.…”
Section: Ddpcr Detection Of Esr1 Mutations In Patient Biopsiesmentioning
confidence: 95%
See 2 more Smart Citations
“…62 There were no pathological complete responses (pCR) in the ERpositive population, and there was no additional suppression of tumor cell proliferation with the addition of MK-2206. A single-arm, phase 2 neoadjuvant clinical trial was conducted using the AKT inhibitor MK-2206 in combination with anastrozole in advanced breast cancer patients with a PIK3CA mutation.…”
Section: Ddpcr Detection Of Esr1 Mutations In Patient Biopsiesmentioning
confidence: 95%
“…A single-arm, phase 2 neoadjuvant clinical trial was conducted using the AKT inhibitor MK-2206 in combination with anastrozole in advanced breast cancer patients with a PIK3CA mutation. 62 There were no pathological complete responses (pCR) in the ERpositive population, and there was no additional suppression of tumor cell proliferation with the addition of MK-2206. 62 Furthermore, a patient in this study acquired an ESR1 mutation detected at the time of surgery.…”
Section: Clinical Implications and Therapeutic Strategies To Treat Mbmentioning
confidence: 95%
See 1 more Smart Citation
“…These findings, together with the upcoming results of the SANDPIPER phase III study (fulvestrant ± taselisib, NCT02340221) in the metastatic setting will help to define the further development of taselisib. Another reported trial in the NA context is the phase II single-arm trial with MK-2206, a pan-AKT inhibitor [36]. Potential eligible patients with clinical stage II/III were preregistered and received anastrozole (plus goserelin if premenopausal) for 28 days in cycle 0, pending tumor PIK3CA analysis.…”
Section: Neoadjuvant Endocrine Therapy As a Platform For New Therapiesmentioning
confidence: 99%
“…These studies identified HER2 mutation and phosphorylation as mechanisms by which ER + HER2 non-amplified (henceforth referred to as ER + HER2 -) breast cancer cells could resist endocrine treatment 2,11 . However, translation of these findings proved challenging with results from clinical trials not living up to preclinical promise 3,6 . There is recognition now that this is likely because only a subset of ER + breast cancers activate HER2 to resist endocrine therapy.…”
Section: Introductionmentioning
confidence: 99%